2022
DOI: 10.3390/polym14173440
|View full text |Cite
|
Sign up to set email alerts
|

Small Diameter Cell-Free Tissue-Engineered Vascular Grafts: Biomaterials and Manufacture Techniques to Reach Suitable Mechanical Properties

Abstract: Vascular grafts (VGs) are medical devices intended to replace the function of a blood vessel. Available VGs in the market present low patency rates for small diameter applications setting the VG failure. This event arises from the inadequate response of the cells interacting with the biomaterial in the context of operative conditions generating chronic inflammation and a lack of regenerative signals where stenosis or aneurysms can occur. Tissue Engineered Vascular grafts (TEVGs) aim to induce the regeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 160 publications
0
9
0
Order By: Relevance
“…Previous studies have reported limited cellular infiltration and integration of PCL/PLCL grafts implanted in arteries, with high rates of thrombosis and neointimal hyperplasia. 20 , 21 Intimal thickening and subsequent vascular remodeling over time can lead to stenosis and occlusion, which are associated with various health risks such as hypertension, myocardial infarction, and stroke. 22 However, this study showed that large-diameter grafts may not cause graft stenosis compared with small-diameter grafts, although there may be some intimal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported limited cellular infiltration and integration of PCL/PLCL grafts implanted in arteries, with high rates of thrombosis and neointimal hyperplasia. 20 , 21 Intimal thickening and subsequent vascular remodeling over time can lead to stenosis and occlusion, which are associated with various health risks such as hypertension, myocardial infarction, and stroke. 22 However, this study showed that large-diameter grafts may not cause graft stenosis compared with small-diameter grafts, although there may be some intimal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Our motivation on BNC-CAGB prosthesis optimization by integrated approaches on guiding endothelial alignment and flow patterns could be successfully realized by using the MMR-Tech technology and thereby effecting the BNC density via the bacterial working cell density on the one hand and via vectored luminal micro topographies on the other hand. Doing so, at first, we addressed the long-lasting and widely investigated roadblock of biomechanical mismatching in between synthetic vascular grafts and the host 5 , 17 , 18 . In contrast to the MMR-Tech derived BNC-CAGB prosthesis that we used in earlier studies 26 – 28 , 45 , we could increase c X_w by two orders of magnitude and advance the biomechanical properties towards artery typical stress-strain relations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, though widely approached, the problem of mechanical mismatching for vascular grafts continues even to advanced approaches that made it to pre-clinical models. To estimate the potential clinical performance, these recently got contrasted to GSV 17 . One step beyond, a very recent study on BNC-CABG grafts used a surgical mesh to reinforce the mechanical properties and showed decreased luminal narrowing in vivo 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, artificial blood vessel grafts to replace autologous blood vessels are being manufactured in the field of tissue engineering [ [9] , [10] , [11] , [12] ]. Due to the high clinical demand for artificial blood vessel grafts, several off-the-shelf products have been developed using synthetic polymers (e.g., polyethylene terephthalate (Dacron) and polytetrafluoroethylene (Teflon) and ePTFE (GORE-TEX)) [ [13] , [14] , [15] , [16] ]. These artificial blood vessel grafts have been able to successfully replace diseased vessels when transplanting medium or large diameter blood vessels [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%